A Study on Callus Induction and the Successful Regeneration of Plantlets from Rhizome Explants of Alpinia galanga (L.) Willd., a Valuable Medicinal Plant - Shamsudheen, Kizhakke Modongal; Mehaboob, Valiyaparambath Musfir; Faizal, Kunnampalli; Raja, Palusamy; Thiagu, Ganesan; Shajahan, Appakan (Asian Journal of Biological and Life Sciences)
Aim: The primary focus of our study is to establish a reliable approach for plant regeneration via indirect organogenesis of Alpinia galanga, utilizing rhizome buds. Materials and Methods: The rhizome explants were placed on MS media supplemented with 0.5 to 2.5 mg/L 2,4-D to induce callus formation. The more effective callus induction was observed on MS media containing 1.5 mg/L 2,4-D with a light green, compact nature of callus. The callus transferred to MS media supplemented with various cytokinin’s such as BAP, Kinetin and TDZ in different concentrations for shoot induction. Results: The highest shoot induction frequency (91.0±3.21%), the maximum number of shoots per callus (9.66±0.88) and the highest plantlet length (91.13±1.44 mm) were observed in 1.0 mg/L BAP. The best-regenerated shoot buds were then transferred to auxins such as NAA and IBA with various concentrations (0.25 mg/L, 0.5 mg/L, 0.75 mg/L and 1.0 mg/L) for root initiation. High rooting frequency (93.00±1.73%), maximum number of roots (21.66±1.76) and maximum root length (93.33±1.76 mm) were induced in MS medium containing 0.5 mg/L IBA. Conclusion: We have developed a reliable and easily replicable protocol for callus induction and subsequent plant regeneration of A. galanga in controlled laboratory settings. Following this, the in vitro plantlets were successfully acclimatized to field conditions.
Keywords: Alpinia galanga; Auxin; Callus; Rhizome